PENGARUH PENGGUNAAN SISTEM INFORMASI AKUNTANSI, VIRAL MARKETING, DAN TAGLINE “GRATIS ONGKIR” TERHADAP IMPULSE BUYING ONLINE PADA KONSUMEN: (STUDI PADA MAHASISWA DI SOLO RAYA) - Desi Aulia Fitri Andriyana; Indra Lila Kusuma; Maya Widyana Dewi (Jurnal Ilmiah Akuntansi, 2024)
This research aims to determine the use of accounting information systems, viral marketing, and the tagline "free shipping" on online impulse buying among consumers. This research uses a quantitative type of research. The population in this study were students in Solo Raya. Sample selection used accidental sampling technique, with a sample size of 100 respondents. The data sources used are primary and secondary data. The data collection method uses a questionnaire or questionnaire. This research uses data analysis methods, namely descriptive statistical analysis, data quality testing, and classical assumption testing. The research results state that the accounting information system has a significant effect on online impulse buying among consumers, viral marketing has a significant effect on online impulse buying among consumers, and the tagline "free shipping" has a significant effect on online impulse buying among consumers.